Pelatihan Pembelajaran Bahasa Inggris Berbasis Kearifan Lokal Lingkungan Bagi Guru Bahasa Inggris Se-Kabupaten Tanah Laut - Yasyir Fahmi Mubaraq; Tri Winindyasari Palupi; Hendera; Yulieda Hermaniar (Jurnal Pemberdayaan Masyarakat, 2025)
This training program, conducted as part of a community service initiative, aims to enhance English teachers’ competencies in integrating local wisdom and environment insight into learning, with an emphasis on teaching practice (peer teaching) and simulations using innovative media. The program was implemented through a series of training sessions that provided each participant with opportunities to practice teaching strategies, develop materials based on regional potential, and design authentic assessments. Pre-test results showed that most teachers were in the moderate category in understanding and applying local wisdom-based learning, with weaknesses in the aspects of authentic evaluation and material format suitability. During the training, the peer teaching model enabled teachers to provide constructive feedback to each other, while innovative media simulations encouraged creativity and technological skills. Questionnaire feedback indicated that teachers felt this method helped “bring the learning context closer to students’ lives.” These findings confirm that combining peer teaching with innovative media simulations is effective in improving teachers’ pedagogical skills while reinforcing the relevance of teaching materials to local contexts.